Reducing Costs of Preventive Lightning Systems by Locational Optimization - Libório,Matheus, (2020)
ABSTRACT The installation of lightning detection sensor systems involves a large volume of resources. However, the absence of these systems can lead to irreparable damage, such as the death of a person. How to reduce the costs of implementing these systems to protect workers and citizens or even public and private equipment? Usually, this problem is not solved on a formal level, but based on the intuition of the involved specialists, without applying optimization techniques. Taking this into account, this research explores the theoretical structure of locational optimization methods to propose a simplified heuristic method that does not require any programming skills for its application. Specifically, its use directly resulted in the cost reduction of preventive lightning systems in an area containing 41 mines. All mines must be covered by the sensor system which has a coverage radius of 10 km. The experimental results demonstrate that the application of this method generates more effective results than those obtained using known methods of locational optimization. The method proposed in this research contributes directly to reduce costs of preventive lightning systems and indirectly to protect workers in mining areas as well as to protect populations in urban areas where the frequency and incidence of lightning is especially high.